2022
DOI: 10.1001/jamanetworkopen.2022.39068
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oncology Advanced Practice Professional Willingness to Participate in Medical Aid in Dying

Abstract: ImportanceIn 2021, New Mexico passed legislation allowing nurse practitioners and physician assistants (referred to herein as advanced practice professionals [APPs]) to prescribe medications for medical aid in dying (MAID). Other US states with existing MAID laws (eg, Washington) are also considering expanding MAID prescribing authority to APPs. There is a lack of research exploring APP knowledge of, willingness to, and comfort with acting as a prescribing or consulting clinician for MAID.ObjectiveTo assess pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This lack of MAID-trained clinicians is in clear contrast to the desire for such training among medical students and residents 3–9 . In studies of Canadian trainees, between 41% and 71% reported being willing to provide MAID care 8,9 .…”
Section: Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of MAID-trained clinicians is in clear contrast to the desire for such training among medical students and residents 3–9 . In studies of Canadian trainees, between 41% and 71% reported being willing to provide MAID care 8,9 .…”
Section: Problemmentioning
confidence: 99%
“…However, physician training in MAID has been largely inadequate to keep pace with the expansion of MAID legalization. In several studies, clinicians have stated that they were ill-equipped to handle a MAID request from a patient, despite being willing to participate in this type of care 2–4 . Although formal national estimates of access to MAID-trained physicians are still needed, qualitative studies suggest significant access gaps 5 .…”
Section: Problemmentioning
confidence: 99%
“…Nurse practitioner participation in medical aid in dying Singer et al (2022) surveyed specialty advanced practice providers (APPs) in Washington state to assess their willingness to participate in MAID. The survey respondents included NPs and PAs who worked mostly in medical oncology, hematology, transplant, and supportive care.…”
Section: Clinical Implementationmentioning
confidence: 99%
“…Of all APPs surveyed, 90.9% either agreed or strongly agreed that MAID should be legal, and the majority agreed that APPs should be included as eligible providers. Regarding their personal participation, 50.6% of respondents reported willingness to participate in MAID, whereas 40.3% were unsure and 9.1% were unwilling to participate (Singer et al, 2022).…”
Section: Clinical Implementationmentioning
confidence: 99%
See 1 more Smart Citation